2020
DOI: 10.2196/18747
|View full text |Cite
|
Sign up to set email alerts
|

Social, Behavioral, and Cultural factors of HIV in Malawi: Semi-Automated Systematic Review

Abstract: Background Demographic and sociobehavioral factors are strong drivers of HIV infection rates in sub-Saharan Africa. These factors are often studied in qualitative research but ignored in quantitative analyses. However, they provide in-depth insight into the local behavior and may help to improve HIV prevention. Objective To obtain a comprehensive overview of the sociobehavioral factors influencing HIV prevalence and incidence in Malawi, we systematicall… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 54 publications
(86 reference statements)
2
25
0
Order By: Relevance
“…The risk of HIV acquisition among infants exposed to HIV in our study was almost two times higher than that observed in South Africa [8] [9] but similar to other studies conducted in Malawi and settings India [10] [11] [16]. Consistent with other studies, the risk of HIV infection of the HEI was higher with older age at DNA-PCR sample collection [12].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The risk of HIV acquisition among infants exposed to HIV in our study was almost two times higher than that observed in South Africa [8] [9] but similar to other studies conducted in Malawi and settings India [10] [11] [16]. Consistent with other studies, the risk of HIV infection of the HEI was higher with older age at DNA-PCR sample collection [12].…”
Section: Discussionsupporting
confidence: 90%
“…Our findings also demonstrate considerable heterogeneity in risk of HIV infection among the HEI in Malawi. Several spatial epidemiological studies indicate spatial variation of diseases which could be attributed to social and cultural factors [14] [15] [16]. Generally, studies of HIV epidemiology in Malawi have been highly predominant in the districts in the southern region followed by the central and northern regions [13] [17].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of HIV acquisition among infants exposed to HIV in our study was almost two times higher than that observed in South Africa 11 12 but similar to other studies conducted in Malawi and India. [13][14][15] Consistent with other studies, the prevalence of HIV infection of the HEI was higher with older age at DNA-PCR sample Open access collection. 16 With the high prevalence of HIV infection being observed among EID in the Northern Region of Malawi, it is imperative to consider the northern region with quality improvement projects aimed at bringing down the HIV infection risk among HEI.…”
Section: Discussionsupporting
confidence: 88%
“…Several spatial epidemiological studies indicate spatial variation of diseases which could be attributed to social and cultural factors. 15 18 19 Generally, studies of HIV epidemiology in Malawi have been highly predominant in the districts in the southern region, followed by the central and northern regions. 17 20 The spatial pattern of the risk of HIV infection would imply the need to target PMTCT interventions in the districts with high risk of paediatric HIV acquisition in order to improve the health of the children and the women.…”
Section: Discussionmentioning
confidence: 99%
“…To identify the RCT studies without the requirement of manual screening, RobotSearch uses a high recall and validated machine learning classifier that is capable of ordering retrieved papers by study sample size and quality (i.e., risk of bias). Similar tools offer efficiency in the searching and study selection stages, where algorithms built in programmes such as Python can narrow down potentially relevant articles in fields where many thousands of articles are published (e.g., HIV [ 25 ]).…”
Section: Operationalising Living Htamentioning
confidence: 99%